Numerical analysis of effect of magnetic field on combined surface tension and buoyancy driven convection in partially heated open enclosure - Nagarajan, N.; Öztop, Hakan Fehmi; Begum, A. Shamadhani; Al-Salem, Khaled (Emerald Group Publishing Ltd, 2015)
Purpose - The purpose of the paper is to investigate the effects of magnetic field on the flow driven by the combined mechanism of buoyancy and thermocapillary flow in an open enclosure with localized heating from below and symmetrical cooling from the sides. Design/methodology/approach - The governing equations are discretized by the control volume method with power-law scheme and solved numerically by SIMPLE algorithm for the pressure-velocity coupling together with under-relaxation technique. Findings - In this work, it is observed that, the average Nusselt number, decreases with an increase of Hartmann number Ha, and increases with increase of Prandtl and Grashof number. At large Marangoni number Ma, a prominent secondary eddies are observed at the top of the enclosure due to the effect of surface tension. Originality/value - The study combines many external forces on thermocapillary flow.
Keywords: Natural convection; Magnetic field; Control volume method; Open enclosure; Thermocapillary flow